2003
DOI: 10.1039/b212865a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of novel thick sol-gel titania film photocatalysts

Abstract: The preparation and characterization of thick (9 microns), clear, mechanically robust and photocatalytically active films of nanocrystalline anatase titania are described. XRD and SEM analysis show the films comprise 13 nm particles of anatase TiO2. Thin (54 nm) films of the 'paste' TiO2, along with sol-gel titania films made by a more traditional route are also prepared and characterised. All titania films mediate the photocatalytic destruction of stearic acid with a quantum yield of 0.0016 +/- 0.0003, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 17 publications
2
104
0
1
Order By: Relevance
“…Wagemaker et al 56 used X-ray absorption to show that Li intercalation results in the occupation of the crystal-field split Ti 3d t(2g) orbitals. From time dependent measurements of the optical absorption and fluorescence of nanocrystalline TiO 2 films under cathodic bias in LiClO 4 propylene carbonate, Kang et al 57 found that as Li + intercalates, electrons fill shallow traps located between 0.1 and 0.6 eV below the conduction band, which is consistent with our calculated binding energy of -0.5 eV. The positive binding energies for the second and third clusters in Table 7 indicate that clusters that carry a high net charge are not favorable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagemaker et al 56 used X-ray absorption to show that Li intercalation results in the occupation of the crystal-field split Ti 3d t(2g) orbitals. From time dependent measurements of the optical absorption and fluorescence of nanocrystalline TiO 2 films under cathodic bias in LiClO 4 propylene carbonate, Kang et al 57 found that as Li + intercalates, electrons fill shallow traps located between 0.1 and 0.6 eV below the conduction band, which is consistent with our calculated binding energy of -0.5 eV. The positive binding energies for the second and third clusters in Table 7 indicate that clusters that carry a high net charge are not favorable.…”
Section: Resultsmentioning
confidence: 99%
“…Anatase is the more stable phase for crystals of nanometer dimensions 2 and is now becoming a technologically important material because of the facile synthesis of nanocrystalline TiO 2 and its applications in areas such as dye-sensitized solar cells (DSSCs) 3 and photocatalysis. 4 Anatase TiO 2 differs from the rutile form in that it has a lower dielectric constant and is less dense, thereby allowing lithium intercalation more readily. 5 In a dye-sensitized solar cell, the nanocrystalline anatase electrode is composed of a porous network of particles of ∼15 nm in diameter, which have been sintered together to ensure electronic contact.…”
Section: Introductionmentioning
confidence: 99%
“…• Built Environment Self-cleaning coatings [34,38,39,[41][42][43][44][45][46][47][48][49][50]. Non-spotting glass [47,51].…”
Section: Titania Applicationsmentioning
confidence: 99%
“…S1a, SI) suggest that Ag/AgCl @ chiral TiO 2 nanofibers contain Ti, O, C, Ag and Cl elements. The C1s was attributed to the adventitious hydrocarbon released from the XPS instrument [27]. In Fig.…”
Section: Characterization Of Ag/agcl @ Chiral Tio 2 Nanofibersmentioning
confidence: 99%
“…by coating a paste of the suspension using the doctor-blade technique [27]. After coating the films were kept in a clean box for 15 min to relax surface irregularities and the residual mechanical stress of the coating.…”
Section: Assembly Of Dsscsmentioning
confidence: 99%